A Constitutive Model for Overconsolidated Structured Soils Using Structural Variable. (10th August 2021) - Li, Wugang; Liu, Wenhua; Xue, Zhijia; Sun, Xiuli
Abstract : Due to the influence of soil structure, structured soils exhibit significantly different mechanical behavior compared to the reconstituted soils having the same material. In this work, a theoretical analysis focusing on the mechanical behavior of structured soils is presented. Based on the mechanical behavior of the structured soil, a newly defined variable structural index was used as a measurement of the integrity of soil structure based on the concept of intrinsic compression line of intact structured soils. Furthermore, a novel correlation for the variation in volume of structured soils is established using effective stress and newly defined structural index as the constitutive variables. The novel correlation provided interpretation about the mechanism of compression behavior of the structured soils. Afterwards, the proposed correlation for the variation in volume was extended to triaxial stress state in the framework of subloading surface to include the effect of overconsolidation. Comparisons between the predictions and experimental results validated the proposed constitutive model for structured soils.